Latency to selective serotonin reuptake inhibitor vs benzodiazepine treatment in patients with panic disorder: a naturalistic study. (5th February 2023) - Piccoli, Eleonora; Bergamaschini, Irma; Molteni, Laura; Vanzetto, Simone; Varinelli, Alberto; Viganò, Caterina; Catania, Gabriele; Baldwin, David S.; Domschke, Katharina; Dell'Osso, Bernardo
Abstract: Background: Panic disorder (PD) is a prevalent and impairing anxiety disorder with previous reports suggesting that the longer the condition remains untreated, the greater the likelihood of nonresponse. However, patients with PD may wait for years before receiving a guideline-recommended pharmacological treatment. The widespread prescription of benzodiazepines (BDZ) for managing anxiety symptoms and disorders might delay the administration of pharmacotherapy according to guidelines (eg, selective serotonin reuptake inhibitors, SSRIs). The present study aimed to determine the mean duration of untreated illness (DUI) in a sample of PD patients, to quantify and compare DUI-SSRI to DUI-BDZ, and to compare findings with those from previous investigations. Methods: Three hundred and fourteen patients with a Diagnostic and Statistical Manual of Mental Disorders, fifth edition diagnosis of PD were recruited from an Italian outpatient psychotherapy unit, and epidemiological and clinical variables were retrieved from medical records. Descriptive statistical analyses were undertaken for sociodemographic and clinical variables, Wilcoxon matched-pair signed rank test was applied to compare the distribution of DUI-SSRI vs DUI-BDZ, and Welch's t test was performed to compare findings with those from previous studies. Results: The mean DUI-SSRI of the total sample was 64.25 ± 112.74 months, while the mean DUI-BDZ was significantly shorter (35.09 ± 78.62 months; P  < 0.0001). A significantly longer DUI-SSRI, compared to findings from previous studies, was also observed. Conclusions: The present results confirm a substantial delay in implementing adequate pharmacological treatments in patients with PD, and highlight the discrepancy between recommendations from international treatment guidelines and common clinical practice in relation to BDZ prescription.